EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TGT DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PRESTASI BELAJAR DAN ASPEK AFEKTIF MATEMATIKA SISWA DITINJAU DARI KECERDASAN MAJEMUK - Fadila, Abi; Budiyono, Budiyono; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to investigate: (1) whose learning achievement and affective aspect of Mathematics are better between the students with the cooperative learning model of the STAD type with contextual approach and those with the cooperative learning model of the TGT type with contextual approach; (2) whose learning achievement and affective aspect of Mathematics are better among the students with mathematical logical intelligence, visual intelligence, kinesthetic intelligence, and interpersonal intelligence; and (3) whether or not there is an interaction in each category of the cooperative learning models and the intelligence types on the learning achievement and affective aspect of Mathematics. This research used the quasi experimental research method. Its population was all of the students in Grade VII of State Junior Secondary Schools of Sukoharjo regency in Academic Year 2012/2013. The samples of the research consisted of 141 students, and they were taken by using the stratified cluster random sampling. The data of the research were gathered through test of learning achievement and questionnaire affective aspect. The proposed hypotheses of the research were tested by using a two-way MANOVA with unbalance cells at the significance level of 5%. The results of the research are as follows 1) The learning achievement in Mathematics of the students of the TGT with contextual approach is better than that STAD with contextual approach, but the affective aspect of Mathematics of the students with TGT with contextual approach is as good as that STAD with contextual approach; 2) The learning achievement in Mathematics of the students with the mathematical logical intelligence is as good as those of the students with the kinesthetic intelligence, interpersonal intelligence but better than visual intelligence, the learning achievement in Mathematics of the students with the kinesthetic intelligence is better than interpersonal intelligence. The affective aspect of Mathematics of the students with the mathematical logical intelligence is as good as that of the students with the kinesthetic intelligence, but better than visual intelligence and interpersonal intelligence, and the affective aspect of Mathematics of the students with the visual intelligence is as good as that of the students with the interpersonal intelligence. 3) There is no any interaction of effect of the cooperative learning models and the multiple intelligences on the learning achievement in Mathematics and the affective aspect of Mathematics.Keywords: STAD, TGT, multiple intelligences, learning achievement, and affective aspect.